2014
DOI: 10.1111/sjop.12183
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive sensitivity, body image dissatisfaction, and body awareness in healthy individuals

Abstract: Relationships among interoceptive sensitivity (IS), body image dissatisfaction, body mass index (BMI), and self-reported body awareness were investigated in a cross-sectional study. Eighty-two Norwegian high school students and 70 Hungarian undergraduate university students participated in the study. Subjects completed two questionnaires (Body Image Ideals Questionnaire - BIQ; Body Awareness Questionnaire - BAQ) followed by the assessment of interoceptive sensitivity using the Mental Tracking Method (MTM). An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 78 publications
9
56
1
3
Order By: Relevance
“…In accordance to Emanuelsen et al ( 2015 ) who showed that body dissatisfaction is related to IAcc in healthy persons, we also observed inverse correlations between IAcc (during “Self”) and body dissatisfaction in this study. As depicted in Figure 2 , the pattern of relationship was quite similar both in the groups of anorexics and in the control group at T1, highlighting that the observed results are comparable between controls and patients, though due to the small sample size more data are needed to support this result.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance to Emanuelsen et al ( 2015 ) who showed that body dissatisfaction is related to IAcc in healthy persons, we also observed inverse correlations between IAcc (during “Self”) and body dissatisfaction in this study. As depicted in Figure 2 , the pattern of relationship was quite similar both in the groups of anorexics and in the control group at T1, highlighting that the observed results are comparable between controls and patients, though due to the small sample size more data are needed to support this result.…”
Section: Discussionsupporting
confidence: 93%
“…The body as object describes an attitude of evaluation of its appearance and a position as if seen through the eyes of others. Similarly, a negative relation has been shown between IAcc and body-image dissatisfaction (Emanuelsen et al, 2015 ) in a sample of 82 high school students (mean age 17). Of relevance, other studies have reported that levels of IAcc influence eating habits, e.g., IAcc is inversely related to intuitive eating (Herbert et al, 2013 ).…”
Section: Introductionmentioning
confidence: 75%
“…Reliability and validity is firmly established and the BIQ correlates strongly with other measures of body image such as the Body Areas Satisfaction Scale (BASS), Situational Inventory of Body-Image Dysphoria (SIBID), and the Appearance Schemas Inventory (cash & szymanski 1995). Reliability of the Hungarian version was appropriate in a past study (emanueLsen et al 2015) and also good in the present study (0.81).…”
Section: Questionnairesmentioning
confidence: 74%
“…The BAQ is con sidered a reliable and valid instrument for measuring self-reported attentiveness to normal bodily processes (mehLing et al 2009). The Hungarian version showed good validity and reliability in past studies (emanueLsen et al 2015;köTeLes 2014). In the present study, the internal consistency of the scale was 0.89.…”
Section: Questionnairesmentioning
confidence: 99%
“…For example, Ainley and Tsakiris (2013) showed that the degree to which individuals are aware of their inner body signals (i.e., Interoceptive Accuracy, IAcc) is inversely correlated with selfobjectification, which is the tendency to experience one's body as an object (Fredrickson & Roberts, 1997). Others have found an inverse relationship with body-image satisfaction (Emanuelsen, Drew, & Kӧteles, 2014): in two samples of healthy participants, results showed that lower interoceptive accuracy, measured using the heartbeat perception task, is associated with higher body dissatisfaction, as evaluated using the Body Image Ideals Questionnaire by Cash and Szymanski (1995). These observations suggest that interoceptive processing extends from the basic levels of multisensory integration to the conscious (affective) attitudes that we hold about our body, highlighting the role of interoception in different hierarchical levels of body-representations.…”
Section: Introductionmentioning
confidence: 99%